PENGARUH LABA DAN KOMPONEN ARUS KAS TERHADAP ARUS KAS MASA DEPAN (Studi Kasus Pada Perusahaan Property and Real Estate yang Terdaftar di Bursa Efek Indonesia Periode tahun 2016 – 2020) - Dhian Andanarini Minar Savitri; Prihasantyo Siswo Nugroho; Ahmad Ulin Nuha (ITB AAS INDONESIA, 2022)
The purpose of this study is to examine and analyze gross profit, operating profit, net profit, operating cash flow, investment cash flow, financing cash flow to future cash flows in non-financial companies in the property and real estate sector listed on the Indonesia Stock Exchange. 2016-2020. The population that is the object of this study is non-financial companies in the property and real estate sector that are members of the Indonesia Stock Exchange during the 2016-2020 period, with a sampling method using purposive sampling. The analysis technique used is the classical assumption test which includes normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. And the sample used in this study amounted to 28 companies, namely from non-financial companies in the property and real estate sector in the Indonesia Stock Exchange during the period 2016-2020. The results showed that: (1) Gross profit has no effect on future cash flows; (2) Operating profit has no effect on future cash flows; (3) Net income has no effect on future cash flows; (4) Operating cash flows have a positive and significant on future cash flows; (5) Investment cash flows have a negative and significant effect on future cash flows; (6) financing cash flows have a negative and significant effect on future cash flows.